Presuppositions in The Judge Film: A Pragmatic Study - Hilda Tri Yulianti; Rohmah, Yuni Syifau; Depi Prihamdani (Journal of English Development, 2026)
This study examines presupposition as a pragmatic phenomenon in film communication, concentrating on its application in the movie The Judge. This research, rooted in pragmatics, seeks to identify the forms of presupposition utilized in the film and to analyze their frequency in cinematic communication. This study utilizes a descriptive qualitative research design to investigate presuppositional statements from The Judge film, directed by David Dobkin. The results indicate that the film encompasses six categories of presupposition: existential, factive, non-factive, lexical, structural, and counterfactual presuppositions. Structural presupposition is the most prevalent type, comprising 36%, followed by factive presupposition at 22.6% and existential presupposition at 17.3%. Although non-factive presupposition (8%) and lexical presupposition (6.6%) are less common, counterfactual presupposition makes up 9.3% of the data. These findings demonstrate that assumption serves as a crucial pragmatic tool in influencing implicit meaning and facilitating effective communication in film discourse.